2021
DOI: 10.1101/2021.11.29.470345
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Structural basis of INTAC-regulated transcription

Abstract: For the majority of expressed eukaryotic genes, RNA polymerase II (Pol II) forms a paused elongation complex (PEC) and undergoes promoter-proximal pausing downstream of the transcription start site 1–3. The polymerase either proceeds into productive elongation or undergoes promoter-proximal premature transcription termination 4–6. It remains incompletely understood how transcription is regulated at this stage. Here, we determined the structure of PEC bound to INTAC, an Integrator-containing PP2A complex 7, at … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 53 publications
2
12
0
Order By: Relevance
“…Previous studies of Integrator recruitment focused on its recruitment to snRNA genes by the RNA Pol II CTD and NELF (Egloff et al, 2007(Egloff et al, , 2010Stadelmayer et al, 2014;Yamamoto et al, 2014). These earlier studies were supported by structural work on Integrator-bound PEC comprised of RNA Pol II and pausing factor NELF (Fianu et al, 2021;Zheng et al, 2021), consistent with a model where Integrator is recruited to promoters of snRNAs and shorter, promoter-proximal, non-coding RNAs by PEC. Unlike Integrator depletion, PAF1 depletion did not regulate these shorter RNAs, suggesting that the PAF1C-regulated longer transcripts are regulated differently from the shorter Integrator substrates processed by Integrator-PEC.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Previous studies of Integrator recruitment focused on its recruitment to snRNA genes by the RNA Pol II CTD and NELF (Egloff et al, 2007(Egloff et al, , 2010Stadelmayer et al, 2014;Yamamoto et al, 2014). These earlier studies were supported by structural work on Integrator-bound PEC comprised of RNA Pol II and pausing factor NELF (Fianu et al, 2021;Zheng et al, 2021), consistent with a model where Integrator is recruited to promoters of snRNAs and shorter, promoter-proximal, non-coding RNAs by PEC. Unlike Integrator depletion, PAF1 depletion did not regulate these shorter RNAs, suggesting that the PAF1C-regulated longer transcripts are regulated differently from the shorter Integrator substrates processed by Integrator-PEC.…”
Section: Discussionmentioning
confidence: 74%
“…More recently, multiple lines of evidence have demonstrated that Integrator functions in terminating PROMPT and eRNA transcription through cleavage of the nascent RNA products and in attenuating coding gene transcription by cleaving short nascent RNAs (Elrod et al, 2019;Lykke-Andersen et al, 2021;Tatomer et al, 2019). Recruitment of Integrator to short nascent transcripts produced at pause sites and at snRNA genes is through the paused transcription complex (PEC) (Egloff et al, 2007;Fianu et al, 2021;Stadelmayer et al, 2014;Yamamoto et al, 2014;Zheng et al, 2021). However, eR-NAs and PROMPTs can be much longer than these short RNAs.…”
Section: Introductionmentioning
confidence: 99%
“…The MBL/β-CASP domain of INTS11 is a bona fide nuclease, but remains in an inactive state until its recruitment to paused RNAPII [ 11 , 18 ]. Two recent cryo-EM structures [ 11 , 14 ] revealed that the KOWx-4 domain of SPT5 (DSIF) pushes against the β-CASP lid of INTS11 ( Figure 3b-c ), opening it and allowing a substrate to engage with the active center [ 11 ]. The RNA exiting the active site of RNAPII is partially protected by the KOWx-4 domain of SPT5 and is guided directly into the active site of INTS11.…”
Section: The Structure Of the Integrator Complexmentioning
confidence: 99%
“…Binding of RNAPII CTD to the Integrator is mediated via a composite interface of INTS4/2/7, which forms a cavity that accommodates the RNAPII CTD with sidechain-specific contacts. Locations of additional peptides are reported by Zheng et al with increasing proximity to the active site of PP2A, suggesting a preferred path of the RNAPII CTD within the Integrator complex [ 14 ]. However, no density could be observed close to the active site of PP2AC [ 11 ].…”
Section: The Structure Of the Integrator Complexmentioning
confidence: 99%
See 1 more Smart Citation